Chinese Proprietary Medicine Xianling Gubao Capsule for Osteoporosis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Cheng, Bai-Ru; Wu, Rou-Yan; Gao, Qin-Yang; Jiang, Kai-Xin; Li, Shuang-Sang; Qi, Shi-Hao; Yuan, Ming-Yi; Liu, Jian-Ping (Frontiers in Endocrinology, 2022)
Abstract Objective To assess the benefit and harm of Chinese medicine Xianling Gubao (XLGB) capsule compared to conventional medication or placebo to inform clinical practice. Methods We included randomized controlled trials (RCTs) with Jadad score ≥3 of XLGB capsule compared to pharmaceutical medication, placebo, or no treatment for primary osteoporosis. We conducted searches in EMBASE, Cochrane CENTRAL, MEDLINE, China National Knowledge Infrastructure, VIP, Wanfang, and Chinese Biomedical Literature Database (Sino-Med) from their inception till November 13th, 2021. Study selection and data extraction were done by two authors independently. The methodological quality of the RCTs was assessed using Cochrane's risk of bias tool. The effect size was presented as risk ratio (RR) or mean difference (MD) with their 95% confidence interval (CI). Results Our searches identified 2292 records and after exclusions, eight trials involving 846 participants were included. There was no statistically significant difference between conventional medications with or without XLGB on new fracture (RR: 0.50, 95% CI: [0.13, 1.87]). Quality of life by SF-36 questionnaire of XLGB plus calcium carbonate, vitamin D3, and calcitriol was improved than that of without XLGB (MD: 6.72 scores, 95% CI: [2.82, 10.62]). XLGB increased bone mineral density similarly as calcium carbonate plus vitamin D3 (MD: 0.21, 95% CI: [-0.16, 0.58]) or as alendronate sodium, calcium carbonate plus vitamin D3 (MD: 0.00, 95% CI: [-0.10, 0.10]), but it had no additional effect as an add-on treatment to conventional medications (MD: 0.13, 95% CI: [-0.12, 0.37]). XLGB relieved pain via visual analog scale more effectively when combined with medications (MD: -1.55 score, 95% CI: [-2.47, -0.63]). XLGB as monotherapy did not increase adverse events (RR: 0.63, 95% CI: [0.28, 1.41]), or as an add-on treatment (RR: 0.25, 95% CI: [0.03, 2.16]). Conclusion This systematic review shows that XLGB capsule appears to be safe and has a beneficial effect on the quality of life and pain relief when used alone or in combination with conventional medications in osteoporosis patients. Further large, rigorous trials are warranted to test its long-term benefit. Keywords: Xianling Gubao capsule; Chinese proprietary medicine; osteoporosis; quality of life; bone mineral density; systematic review; meta-analysis